Changes in cell proliferation, but not in vascularisation are characteristic for human endometrium in different reproductive failures: a pilot study - Germeyer, Ariane; Wolff, Michael von; Jauckus, Julia; Strowitzki, Thomas; Sharma, Tanuj; Grazul-Bilska, Anna T. (Reproductive biology and endocrinology, 2010)
Reproductive failure, determined as recurrent spontaneous abortions (RSA) or recurrent implantation failure (RIF) in women is not well understood. Several factors, including embryo quality, and cellular and molecular changes in endometrium may contribute to the insufficient feto-maternal interaction resulting in reproductive failure. Prior clinical studies suggest an inadequate endometrial growth and development of the endometrium, leading to a lesser endometrial thickness.
Gesehen am 01.03.2023